Solving 3D coverage problem using genetic algorithms in wireless camera-based sensor network modelling - Velasco, Neil Oliver M. (Animo Repository, 2019)
Wireless camera sensor networks are used mostly in research today. However, the camera location in a space of study is a problem in maximizing the coverage of the camera. Instead of being a 2D computation, this computation is modeled in 3D projected to 2D walls. This research makes use of Genetic Algorithms - a search optimization algorithm to find the best placement of camera which will yield to a maximum coverage ratio. The results of the experiment show the length of time the algorithm computed, and the obtained the least number of cameras needed for the most coverage.© 2019 IEEE.